2015
DOI: 10.1021/acs.jmedchem.5b00470
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship and Pharmacokinetic Studies of 1,5-Diheteroarylpenta-1,4-dien-3-ones: A Class of Promising Curcumin-Based Anticancer Agents

Abstract: Forty-three 1,5-diheteroaryl-1,4-pentadien-3-ones were designed as potential curcumin mimics, structurally featuring a central five-carbon dienone linker and two identical nitrogen-containing aromatic rings. They were synthesized using a Horner–Wadsworth–Emmons reaction as the critical step and evaluated for their cytotoxicity and antiproliferative activities toward both androgen-insensitive and androgen-sensitive prostate cancer cell lines and an aggressive cervical cancer cell line. Most of the synthesized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Curcumin was synthesized by Claisen-Schmidt condensation of aromatic aldehyde with acetylacetone according to the procedure described in the literature [31]. 1-Alkyl-1 H -imidazole-2-carbaldehydes ( 36 - 49 ) and 1-alkyl-1 H -benzo[d]imidazole-2-carbaldehydes ( 60 - 65 ) were synthesized according to the procedure described in the literature [12,13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin was synthesized by Claisen-Schmidt condensation of aromatic aldehyde with acetylacetone according to the procedure described in the literature [31]. 1-Alkyl-1 H -imidazole-2-carbaldehydes ( 36 - 49 ) and 1-alkyl-1 H -benzo[d]imidazole-2-carbaldehydes ( 60 - 65 ) were synthesized according to the procedure described in the literature [12,13]. …”
Section: Methodsmentioning
confidence: 99%
“…Extensive research in this field has been conducted by several groups in search for effective curcumin-based anti-cancer agents with favorable safety profiles [10,11]. We have recently identified that (i) 1,5-diheteroarylpenta-1,4-diene-3-ones, exemplified by compounds 2 and 3 in Figure 1, serve as an optimal scaffold for developing potential curcumin-based anticancer agents due to their appreciably enhanced in vitro potency relative to curcumin; and (ii) (1 E ,4 E )-1,5-bis(2-methyl-4-(trifluoromethyl)thiazol-5-yl)penta-1,4-dien-3-one ( 2 ) is a very promising lead compound because of its good in vitro potency and attractive in vivo pharmacokinetic profiles [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, in our previous studies, 1-alkyl-1 H -imidazol-2-yl and 1-alkyl-1 H -benzo[ d ]imidazole-2-yl serve as optimal heteroaromatic rings for the antiproliferative potency of 1,5-diheteroarylpenta-1,4-dien-3-ones (e.g. 3 and 4 ) 19 and 1,7-diheteroarylhepta-1,4,6-trien-3-ones (e.g. 5 and 6 ).…”
Section: Resultsmentioning
confidence: 95%
“…24,25 1-Alkyl-1 H -benzo[ d ]imidazole-2-carbaldehydes ( 27-31 ) were obtained from benzene-1,2-diamine and glycolic acid through a three-step transformation as previously reported by us. 19 Other starting carbaldehydes were purchased from Fisher Scientific. 1,3-Bis(diethylphosphonato)acetone ( 58 ) was readily synthesized from carbazic acid methyl ester, 1,3-dichloroacetone, and triethyl phosphite according to the reported procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation